2008
DOI: 10.3399/bjgp08x299281
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of GPs' explanations about mental health problems: development, reliability, and validity of a measure

Abstract: BackgroundHow GPs understand mental health problems determines their treatment choices; however, measures describing GPs' thinking about such problems are not currently available. AimTo develop a measure of the complexity of GP explanations of common mental health problems and to pilot its reliability and validity. Design of studyA qualitative development of the measure, followed by inter-rater reliability and validation pilot studies. SettingGeneral practices in North London.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…No association was found for postgraduate mental health qualifications. More recently, it has been shown that FPs with more complex psychosocial explanations of common mental disorders had greater interest, more training in mental health, and more positive attitudes to depression [25], using a composite of the four DAQ components identified by Botega et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…No association was found for postgraduate mental health qualifications. More recently, it has been shown that FPs with more complex psychosocial explanations of common mental disorders had greater interest, more training in mental health, and more positive attitudes to depression [25], using a composite of the four DAQ components identified by Botega et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, study GPs were self-selected volunteers who may have been more experienced and positive about working with patients with mental health problems and specifically more interested in ways of understanding patients' problems. 28 Thus, there are questions about the generalisability of the study findings to the full range of GPs and patients with mental health problems.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…The Craft of Generalism has the potential to define and protect the whole of medicine and the people it serves from fragmentation. 84,90,91 The Craft of Generalism is a philosophical commitment to breadth of scope (Whole Person Scope), relationship as process (Relational Process), healing and health as a dynamic priority (Healing Orientation) and integration and interpretation of complexity as knowledge management (Integrative Wisdom). In a reductionist or constructivist world, the Craft of Generalism names something highly valuable to the community: care for the whole person.…”
Section: Craft Of Generalism: Protecting the Wholementioning
confidence: 99%